Urgensi Organisasi Pelajar dalam Pengembangan Karakter Kepemimpinan Perspektif Teori Gibson di SMK Al-Futuh Tikung Lamongan - Fatmala, Eka; Ikmal, Hepi; Wahyudi, Winarto Eka (LP3M Universitas Islam Zainul Hasan Genggong, 2022)
Student Organizations have a very large role in the development of student leadership character. The purpose of this study was to examine the urgency of student organizations in developing Gibson's theoretical leadership character at SMK Al Futuh Tikung Lamongan using qualitative research and approaches in the form of observation, interviews, and documentation. The results of this study, the first is the activities of the NU Student Association student organization at Al Futuh Vocational School, the leadership character which is carried out by paying attention to three main components namely personality, motivation and ability has been carried out well by students who are members of student organizations, these three components penetrate each other and influence each other so that they can develop good student leadership characters and the third is the urgency of student organizations in developing student leadership characters as student organizations, student regeneration and student struggle guidelines.